Physiological pharmacology. a comprehensive treatise - Root, Walter S. (Walter Stanton), 1902-1972; Hofmann, Frederick G. (Physiological Pharmacology, 1963)
Physiological Pharmacology: A Comprehensive Treatise, Volume I: The Nervous System - Part A, Central Nervous System Drugs focuses on the influence of drugs on the functions of the central nervous system. The selection first offers information on absorption, distribution, and elimination and effects upon physiological systems. Discussions focus on factors that disturb normal sequence of uptake and elimination of volatile drugs; variations in distribution due to systemic effects of anesthetics; factors influencing the uptake of gases by tissues; and theories of general anesthesia. The book also.